Foreign accent - Moyer, Alene (Cambridge University, 2014)
Includes bibliographical references (pages 184-216) and index; 1. The scope and relevance of accent -- 2. Accent and age -- 3. Accent and the individual -- 4. Accent and society -- 5. Accent and the law -- 6. Accent and instruction -- 7. Conclusions